Strategi Inovatif Meningkatkan Kapasitas Tekno-Pedagogik Guru TK Al-Wahdah dengan Pelatihan Penggunaan Kecerdasan Buatan Chatgpt untuk Mendukung Pembelajaran Kreatif: Penelitian - Edy Sofyan; Ernandia Pandikar; Wawa Puja Prabawa; Rina Marlina (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to explore the effectiveness of artificial intelligence (AI)-based training, especially ChatGPT, in increasing the techno-pedagogic capacity of Al-Wahdah Kindergarten teachers in the city of Bandung. This training is designed using a hands-on-based interactive workshop approach, which allows teachers to directly practice the use of ChatGPT in designing teaching materials that suit the needs of early childhood. Evaluation is carried out through pre-test and post-test to measure the improvement of teachers' skills in the use of technology. The results showed that the average teacher's pre-test score was 50, which increased to 85 on the post-test, showing an increase of 70%. In addition, 90% of participants reported increased confidence in using AI technology to design more creative and interactive teaching materials. Although this training has succeeded in improving teachers' technical skills, challenges such as limited access to technology devices and infrastructure in schools are obstacles to the long-term application of this technology. Therefore, ongoing support and adequate infrastructure are needed to ensure long-term success.